Effects of Surface Soil Temperature on Cassava Physiology under Different Water Regimes - Pipatsitee, Piyanan; Praseartkul, Patchara; Taota, Kanyarat; Ponganan, Navavit; Kongpugdee, Sumaid; Sakulleerungroj, Kampol; Eiumnoh, Apisit (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
The effect of surface soil temperature on cassava physiological characteristics under different water regimes was studied. The aim of this research was to study the relationship between the surface soil temperature and cassava physiological characteristics under irrigated and non-irrigated conditions. The field experiment plots were conducted in Khon Kaen province. The surface soil temperatures and plant physiology during the three to five months after growing were measured using infrared thermography and Licor 6400XT, respectively. The data were then compared and correlated between different water regimes. The results showed that the surface soil temperature of the non-irrigated plot was higher than the irrigated plot. A negative correlation was observed among surface soil temperature, net photosynthesis, stomatal conductance and transpiration rate. However, the positive correlation between the surface soil temperature, the air vapor pressure deficit and the leaf temperature were detected. The critical of surface soil temperature affected to the cassava physiological characteristics was at about 30°C. When the surface soil temperature increased more than 30°C, the air vapor pressure deficit and the leaf temperature increased, while the net photosynthesis, stomata conductance and transpiration rate were gradually decreasing. Therefore, the surface soil temperature was an important factor affecting cassava physiology and growth development. Water and soil management, therefore could reduce surface soil temperature in hot season and leading to good growth development and yield increasing. Keywords: Infrared thermography, Cassava, Plant physiology, Surface soil temperature